Person-directed burnout intervention for nurses: A systematic review of psychoeducational approaches - Ili Binti Abdullah Sharin; Norehan Binti Jinah; Pangie Anak Bakit; Izzuan Khirman Bin Adnan; Nor Haniza Binti Zakaria; Siti Zubaidah Binti Ahmad Subki; Nursyahda Binti Zakaria; Kun Yun Lee (PLoS ONE, 2025)
Background Nurse burnout is a pervasive issue impacting their well-being and patient care quality. Recognized by the World Health Organization as an “occupational phenomenon,” burnout results from inadequately managed chronic workplace stress and manifests as emotional exhaustion, depersonalization, and reduced personal accomplishment. This can lower the quality of life and increase turnover. Effective interventions are vital to overcome nurse burnout and its consequences. Objective This systematic review explored and analyzed the effectiveness of person-directed psychoeducational interventions in reducing nurse burnout. Materials and methods A comprehensive search of five databases was conducted for studies published between 2014 and 2023, following PRISMA guidelines. Eligible studies that reported outcomes of psychoeducational interventions using validated evaluation tools were included. Data were extracted using standardized forms, and quality was assessed with Joanna Briggs Institute critical appraisal tools. A thematic narrative synthesis was performed. Results 27 studies met the inclusion criteria. Interventions including mindfulness-based interventions and cognitive-behavioral therapy, delivered either in combination or on their own, were shown to be effective in reducing nurses’ burnout in 24 studies. However, the sustainability of these effects varied, with limited long-term follow-up data. Additionally, delivery formats (physical, digital, or combined), also influenced effectiveness, suggesting the importance of tailored interventions to specific contexts and needs of the target population. Conclusions Psychoeducational interventions effectively reduce nurse burnout but need further investigation to ensure long-term sustainability. Future research should target diverse settings, incorporate objective and subjective outcome measures, and explore a broader range of interventions to strengthen evidence of burnout management strategies.